Optimizing irradiation dose for Drosophila melanogaster males to enhance heterospecific Sterile Insect Technique (h-SIT) against Drosophila suzukii - Flavia Cerasti; Valentina Mastrantonio; Alessia Cemmi; Ilaria Di Sarcina; Massimo Cristofaro; Daniele Porretta (PLoS ONE, 2025)
The spotted-wing drosophila (Drosophila suzukii), a highly invasive agricultural pest, poses significant challenges to fruit production worldwide. Traditional chemical control methods are costly and raise concerns about resistance and environmental sustainability. The Heterospecific Sterile Insect Technique (h-SIT) has emerged as a promising alternative. Sterile heterospecific males (Drosophila melanogaster) can be used to suppress D. suzukii populations through reproductive interference, primarily mediated by post-zygotic isolation mechanisms. Although this approach ensures the absence of viable offspring from heterospecific matings, male sterilization through irradiation remains essential. It prevents unintended ecological effects from D. melanogaster proliferation in the release area and allows for safe large-scale implementation. Therefore, determining an optimal irradiation dose is critical for achieving high levels of male sterility and maintaining biological quality and mating performance. This study aimed to determine the optimal irradiation dose by assessing induced sterility in D. melanogaster males exposed to gamma ray doses ranging from 80–180 Gy. Subsequently, the longevity and the time spent by irradiated D. melanogaster males courting D. suzukii females were also assessed. Results showed a significant dose-dependent increase in induced sterility, with near-complete sterility at 180 Gy. However, longevity decreased with increasing doses, with males irradiated at 160–180 Gy showing a lifespan reduction of up to 50 days compared to controls. Regardless of the irradiation dose received, D. melanogaster males retained their courtship ability toward D. suzukii females, although males exposed to 160 Gy exhibited reduced courtship activity. These findings showed that, among the tested doses, 80 Gy was the most effective in preserving male longevity and mating performance, significantly reducing fertility, while 180 Gy induced the highest sterility. The potential lifespan and courtship behavior trade-offs warrant further evaluation. Future studies should evaluate field performance to refine the balance between sterility, longevity, and mating performance for effective D. suzukii population suppression.